CytoMatrix for a reliable and simple characterization of lung cancer stem cells from malignant pleural effusions. Issue 3 (9th August 2019) - Bruschini, Sara; di Martino, Simona; Pisanu, Maria Elena; Fattore, Luigi; De Vitis, Claudia; Laquintana, Valentina; Buglioni, Simonetta; Tabbì, Eugenio; Cerri, Andrea; Visca, Paolo; Alessandrini, Gabriele; Facciolo, Francesco; et al.
Abstract: Cancer stem cells (CSCs) are a subpopulation with the properties of extensive self‐renewal, capability to generate differentiated cancer cells and resistance to therapies. We have previously shown that malignant pleural effusions (MPEs) from patients with non‐small‐cell lung cancer (NSCLC) represent a valuable source of cancer cells that can be grown as three‐dimensional (3D) spheroids enriched for stem‐like features, which depend on the activation of the Yes‐associated protein‐transcriptional coactivator with PDZ‐binding motif (YAP‐TAZ)/Wnt‐βcatenin/stearoyl‐CoA desaturase 1 (SCD1) axis. Here, we describe a novel support, called CytoMatrix, for the characterization of limited amounts of cancer cells isolated from MPEs of patients with NSCLC. Our results show that this synthetic matrix allows an easy and fast characterization of several epithelial cellular markers. The use of CytoMatrix to study CSCs subpopulation confirms that SCD1 protein expression is enhanced in 3D spheroids when compared with 2D adherent cell cultures. YAP/TAZ nuclear‐cytoplasmic distribution analysed by CytoMatrix in 3D spheroids is highly heterogeneous and faithfully reproduces what is observed in tumour biopsies. Our results confirm and extend the robustness of our workflow for the isolation and phenotypic characterization of primary cancer cells derived from the lung MPEs and underscore the role of SCD1. Abstract : Malignant pleural effusions (MPEs) are a good source of lung cancer cells and represent an excellent model to investigate tumour heterogeneity. MPE‐derived tumour cells can be grown as three‐dimensional (3D) spheroids enriched for stem‐like properties. CytoMatrix is a reliable support for the characterization of primary 2D and 3D MPE‐derived cell cultures using minimum amount of biological material.